STRES DALAM KARYA SENI LUKIS KONTEMPORER - Andreas Heriansyah; Erfahmi Erfahmi; Yasrul Sami (Serupa The Journal of Art Education, 2020)
This final work visualizes the expression of stress, with human objects in contemporary painting. The visualization of this work is expected to be able to have a positive influence, in evaluating problems faced by themselves and the surrounding social environment, through contemporary painting. The methods and processes used in the creation of a work include several stages: (1) preparation; (2) elaboration; (3) synthesis; (4) concept realization; (5) finising; the discussion of paintings includes the expression of human beings who experience psychological disorders in the form of stress. The titles of the work produced are: (1) Kurekah, (2) Blind me, (3) I want to stretch, (4) But it feels hot, (5) Try to be silent, (6) But the burden is where, (7) Break it , (8) Tie me up, (9) Forced me to see, (10) If God is still here.Kata Kunci : ekspresi stress,seni lukis.